Employment and Unemployment Experiences of Sports Faculty Graduate Women - Ekin BÜYÜKAKTEN; Muazzez ŞAŞMAZ ATAÇOCUĞU (ümit doğan üstün, 2022)
This study aimed to analyze employment and unemployment experiences of sports faculty graduate women. Most of the literature on women in sports have been written with a feminist theory perspective as part of gender studies. Here, macroeconomic parameters and labor theories were prioritized in the analysis of employment and unemployment experiences of women in the sports industry. Semi-structured interviews were conducted online via Zoom with 22 women from different backgrounds, cities, universities, and ages. A qualitative research method was used, and a content analysis was conducted on the transcribed interviews, which revealed the themes in the study. Following themes were found as a result of the findings: education's role in employment and unemployment, gender's role in employment and unemployment, wage and social security issues in employment and unemployment experiences, perception of favoritism, and employment policies. Almost every participant underlined the fact that women in sports, if they educated themselves well enough, under the equal employment opportunities, will be able to find a job. Besides, every one of the participants pointed out that favoritism is the main problem surrounding the sports sector across all areas of work. Women in sports are challenged with housework and childcare in addition to their mostly physical work in their jobs. Women are faced with limitations on finding a job in the public sector and with obstacles, especially in terms of wages, in the private sector causing women either to be unemployed for years or working in jobs for unlawful hours for low wages. This study draws attention to the structural changes in governments, municipalities, federations, sports clubs, and universities that is needed for women to have a transparent and equal future in sports.